GRK5 – A Functional Bridge Between Cardiovascular and Neurodegenerative Disorders - Hendrickx, Jhana O.; van Gastel, Jaana; Leysen, Hanne; Santos-Otte, Paula; Premont, Richard T.; Martin, Bronwen; Maudsley, Stuart (Frontiers in Pharmacology, 2018)
Complex aging-triggered disorders are multifactorial programs that comprise a myriad of alterations in interconnected protein networks over a broad range of tissues. It is evident that rather than being randomly organized events, pathophysiologies that possess a strong aging component such as cardiovascular diseases (hypertensions, atherosclerosis, and vascular stiffening) and neurodegenerative conditions (dementia, Alzheimer’s disease, mild cognitive impairment, Parkinson’s disease), in essence represent a subtly modified version of the intricate molecular programs already in place for normal aging. To control such multidimensional activities there are layers of trophic protein control across these networks mediated by so-called “keystone” proteins. We propose that these “keystones” coordinate and interconnect multiple signaling pathways to control whole somatic activities such as aging-related disease etiology. Given its ability to control multiple receptor sensitivities and its broad protein-protein interactomic nature, we propose that G protein coupled receptor kinase 5 (GRK5) represents one of these key network controllers. Considerable data has emerged, suggesting that GRK5 acts as a bridging factor, allowing signaling regulation in pathophysiological settings to control the connectivity between both the cardiovascular and neurophysiological complications of aging.